Improving Purity of Maleic Anhydride Production by Multi-stage Distillation - Asyfianto, Muhammad Askal; Kristiana, Dila; Larasati, Nadya Dewi; Fairuzza, Shafyna (Journal of Chemical Engineering Research Progress, 2025)
The maleic anhydride production via benzene oxidation is a highly exothermic reaction which causes the product temperature will increase then it needs to be cooled down with a heat exchanger. The modification process is needed to improve the purity of the maleic anhydride process by adding stage of distillation. Maleic anhydride with lower purity from the first distillation is then distilled again in order to improve its purity. The process modification was simulated using Aspen HYSYS and the comparison of maleic anhydride purity between the basic and the modified process is shown in the form of table based on the material stream. The results obtained that the purity of maleic anhydride for both basic and modified process is about 62.64% and 97.72%. This shows that the modified process has higher maleic anhydride purity compared to the basic process as the purity is closer to 100%. Therefore, this modification increases the maleic anhydride purity of the production through benzene oxidation process. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).